The influence and usage of technologies by practicing nurses in Nigeria - Chukwuemeke, Adishi Monday Ayedu; Oniovo, Agbedia Clara (International Journal of Medical and Health Sciences Research, 2023)
Recent medical scientific advancement in e-health is influencing the art and science of nursing globally. While the use of modern technology is visible and appreciated in developed countries, such assertion is still in infancy in Nigeria. There is a dearth of research on the impact of the usage and perceived benefits of existing technologies in the practice of nursing in Nigeria. This is the premise for this study. The main objective of this study is to assess the usage and perceived benefits of existing technologies in the practice of nursing with the view to improving quality of care through adequate usage, and maintenance, more importantly informing other stakeholders on the importance of ensuring adequate supply of existing and emerging technologies. The research design is descriptive and cross-sectional. Respondents were drawn from five (5) selected hospitals each from the Northern and Southern parts of Nigeria through stratified random sampling techniques. A total of 300 nurses were selected from both regions. The quantitative data were analyzed, using Analysis of Variance (ANOVA) with a 95% confidence of 0.05 level of significance. The result of this study emphasized the importance of improving nursing care through efficient and effective usage of technologies, as well as the need for adequate availability and functionality of existing tools used by practicing nurses in Nigeria.